CORRELATION BETWEEN THE ROLE OF NURSE AS EDUCATOR AND SELF CARE BEHAVIOUR IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AT INTERNAL MEDICINE UNIT OF BINA SEHAT HOSPITAL JEMBER - Rima Ulfa Fahra; Nur Widayati; Jon Hafan Sutawardana (NurseLine Journal, 2017)
Diabetes mellitus (DM) is a chronic disease that requires continuous self-care. Education by nurses can support self-care behavior of patients with type 2 DM. Good knowledge affects self-care of type 2 diabetes patients so that metabolic control can be achieved. This study aimed to identify the correlation between the role of nurse as educator and self-care behaviour in patients with type 2 diabetes mellitus. This research applied a descriptive analytic design with cross sectional approach. A total of 63 respondents were enrolled in this study by using consecutive sampling technique. Data collection was conducted by administering questionnaires of nurse role as educator and Summary of Diabetes Self Care Activities (SDSCA). Data were analyzed by using Spearman correlation test with significance level of 0.05. The result showed that the mean value of nurse role and self-care behaviour was 59.84 and 3.79 respectively. The p value was 0.000 (p<0.05) with the correlation coefficient (r) of 0.851. It indicates that there was a significant correlation between nurse role as educator and self-care behaviour in patients with type 2 DM. The correlation was strong and positive which means the better the nurse's role as educator the better the patient's self-care behaviour. The education gained by the patients can affect the motivation to perform self-care behaviour. This study suggests the importance of nurse role in providing education in type 2 diabetes patients to optimize self-care behaviour.